Development of a highly specific serodiagnostic ELISA for West Nile virus infection using subviral particles - Maezono, Keisuke; Kobayashi, Shintaro; Tabata, Koshiro; Yoshii, Kentaro; Kariwa, Hiroaki (Scientific reports, 2021)
West Nile virus (WNV), a member of the Japanese encephalitis virus (JEV) serocomplex group, causes lethal encephalitis in humans and horses. Because serodiagnosis of WNV and JEV is hampered by cross-reactivity, the development of a simple, secure, and WNV-specific serodiagnostic system is required. The coexpression of prM protein and E protein leads to the secretion of subviral particles (SPs). Deletion of the C-terminal region of E protein is reported to affect the production of SPs by some flaviviruses. However, the influence of such a deletion on the properties and antigenicity of WNV E protein is unclear. We analyzed the properties of full-length E protein and E proteins lacking the C-terminal region as novel serodiagnostics for WNV infection. Deletion of the C-terminal region of E protein suppressed the formation of SPs but did not affect the production of E protein. The sensitivity of an enzyme-linked immunosorbent assay (ELISA) using the full-length E protein was higher than that using the truncated E proteins. Furthermore, in the ELISA using full-length E protein, there was little cross-reactivity with anti-JEV antibodies, and the sensitivity was similar to that of the neutralization test.